Structural and photoluminescent studies of non-centrosymmetric manganese(II) N-(2-pyridylmethyl)-(L)-alanine) dicyanamide - Ndosiri, Bridget Ndoye; Nono, Katia Nchimi; Awawou, Paboudam Gbambie; Nfor, Emmanuel Ngwang; Mohamadou, Aminou; Marrot, Jerome; Teke, Peter Ndifon (European Journal of Chemistry, 2019)
The dinuclear compound, [Mn2(Pyala)2(Dca)2(H2O)]n·2H2O (1) (Pyala = N-(2-pyridylmethyl)-L-alanine and Dca = dicyanamide anion) has been synthesized and characterized by elemental analysis, IR and single crystal X-ray diffraction techniques. The crystal data for C22H26Mn2N10O6: orthorhombic, space group P212121 (no. 19), a = 10.3728(8) Å, b = 15.9780(12) Å, c = 16.3585(13) Å, V = 2711.2(4) Å3, Z = 4, T = 198(2) K, μ(MoKα) = 0.989 mm-1, Dcalc = 1.559 g/cm3, 129607 reflections measured (3.564° ≤ 2Θ ≤ 60.046°), 7923 unique (Rint = 0.0324, Rsigma = 0.0155) which were used in all calculations. The final R1 was 0.0169 (I > 2σ(I)) and wR2 was 0.0458 (all data). The obtained non-centrosymmetric dinuclear Mn(II) complex contains two unique Mn(II) cations with similar octahedral coordination environment. Photoluminescent measurements on the complex in the solid state show that it displays strong photoluminescence at 442 nm.